Communications Effectiveness of Agricultural Extension Group in Enbal Cassava Processors In Debut Village, In Southeast Maluku District - Far Far, Risyart Alberth (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Enbal is a product of processed bitter cassava (Manihotesculenta Crantz) which is a traditional food typical of the people (Kei) of the Southeast Maluku Regency. This study aims to analyze the effectiveness of agricultural extension communication between the enbal cassava processing group, and to analyze the effect of farmer participation on the effectiveness of the agricultural extension communication to the enbal cassava processing group in Ohoi Debut, Southeast Maluku Regency. The results showed that the extension planning activity that had the highest average score was determining the meeting location for counseling followed by aspects of determining extension participants, compiling extension materials and developing extension methods. Extension activities that have the highest average score are providing data/information, followed by giving comments/opinions, taking notes, preparing facilities and infrastructure, re-explaining unclear descriptions/opinions and summarizing material descriptions. The results of the analysis explain that there is a positive and significant relationship between land area income, and business experience with extension participation in the planning and implementation of agricultural extension. The level of effectiveness of extension communication is in the high or effective category. The level of counseling participation is positively and significantly related to the effectiveness of counseling communication in cognitive and behavioral aspects.